Is the tapeworm able to affect tissue Pb-concentrations in white rat? - ČADKOVÁ, ZUZANA; MIHOLOVÁ, DANIELA; SZÁKOVÁ, JIŘINA; VÁLEK, PETR; JANKOVSKÁ, IVANA; LANGROVÁ, IVA (Parasitology, 2014)
The effect of gastrointestinal helminths on Pb accumulation in the host body is ambiguous. A laboratory experiment with Rattus norvegicus/Hymenolepis diminuta model was conducted to determine Pb toxicokinetics in a terrestrial host-parasite system. The ET-AAS or ICP–OES techniques were used to determine Pb concentrations (CPb) in both tapeworms and host tissues (kidney, liver, bone, testes, muscle and intestinal wall). Concerning the entire host-parasite system, the highest CPb were detected in H. diminuta. Rat kidneys and bone were the only two tissues whose mean Pb levels were lower in parasitized animals than they were in non-infected subjects after both levels of exposure. At low Pb exposure, parasitization slightly changed the Pb toxicokinetics in the host body. However, with respect to tissue at the same exposure level, no significant differences were detected between the parasitized and non-parasitized animals and no significant correlations were found between CPb in tapeworms and those of host tissues. The results of this study indicate that H. diminuta does not protect rat from elevated Pb exposure even if tapeworm accumulates a higher portion of ingested Pb dose compared with that of the most Pb-loaded host soft tissue. The portion of Pb dose accumulated in H. diminuta correlates positively with parasite biomass.